Impaired emotional empathy and related social network deficits in cocaine users. (25th June 2013) - Preller, Katrin H.; Hulka, Lea M.; Vonmoos, Matthias; Jenni, Daniela; Baumgartner, Markus R.; Seifritz, Erich; Dziobek, Isabel; Quednow, Boris B.
Abstract Chronic cocaine users consistently display neurochemical and functional alterations in brain areas involved in social cognition (e.g. medial and orbitofrontal cortex). Although social functioning plays a crucial role in the development and treatment of drug dependence, studies investigating social cognition in cocaine users are lacking. Therefore, we investigated mental perspective taking ('theory of mind') and emotional and cognitive empathy in recreational (RCU) and dependent (DCU) cocaine users. Furthermore, we related these measures to real‐life indicators of social functioning. One‐hundred cocaine users (69 RCU, 31 DCU) and 68 stimulant‐naïve healthy controls were tested with the Multifaceted Empathy Test (MET), Movie for the Assessment of Social Cognition (MASC) and Reading the Mind in the Eyes Test (RMET). The Social Network Questionnaire was conducted to assess social network size. Furthermore, participants provided information on committed criminal offenses. RCU and DCU showed less emotional empathy compared to controls (MET), whereas cognitive empathy was not impaired (MET, RMET). Additionally, DCU made more errors in mental perspective taking (MASC). Notably, cocaine users committed more criminal offenses and displayed a smaller social network and higher cocaine use was correlated with less social contacts. Diminished mental perspective taking was tentatively correlated with more intense cocaine use as well. Finally, younger age of onset of cocaine use was associated with more pronounced empathy impairment. In conclusion, social cognition impairments in cocaine users were related to real‐life social functioning and should therefore be considered in therapy and prevention strategies.